Landscape heterogeneity shapes bird phylogenetic responses at forest–matrix interfaces in Atlantic Forest, Brazil - Adorno, Bruno F. C. B.; Barros, Fábio M.; Cezar Ribeiro, Milton; Silva, Vinícius X.; Hasui, Érica (Biotropica, 2021)
Agricultural intensification is one of the major factors driving biodiversity loss. However, most studies in human‐dominated landscapes have used taxonomic diversity in their analysis, ignoring evolutionary relationships. Consequently, the relationship between landscape structure and phylogenetic diversity is not well understood. Here, we tested the hypothesis that landscape heterogeneity is positively related to bird phylogenetic indexes of diversity and structure, leading to over‐dispersed phylogenies in very heterogeneous landscapes. We analyzed phylogenetic responses in interfaces between forest edges and anthropogenic matrices (forest–pasture and forest–eucalyptus) using generalized linear mixed models. We also compared these indexes between land covers to assess which one best preserves the phylogenetic history of communities. We used both traditional phylogenetic indexes and those corrected for species richness. Our results showed that phylogenetic diversity varied significantly between land cover types, but this did not occur when we removed effects associated with species richness, suggesting that all land covers preserve similar levels of evolutionary history. Additionally, our best models showed a positive relationship between landscape heterogeneity and bird phylogenetic indexes of diversity and structure, but the strength of these relationships may be land cover dependent. In summary, our work highlights the influence of landscape heterogeneity on the phylogenetic diversity and structure of bird communities, reinforcing the need for its incorporation into conservation‐based studies. in Portuguese is available with online material RESUMO A intensificação agrícola é uma das principais causas relacionadas à perda de biodiversidade. Entretanto, a maioria dos estudos realizados em paisagens dominadas pelo homem costuma usar apenas índices taxonômicos, ignorando as relações evolutivas entre as espécies. Consequentemente, a relação entre estrutura da paisagem e diversidade filogenética não é bem compreendida. Nesse estudo, testamos a hipótese de que a heterogeneidade da paisagem é positivamente relacionada aos índices filogenéticos de diversidade e estrutura das comunidades de aves, o que induz a presença de filogenias dispersas em paisagens muito heterogêneas. Nós analisamos as respostas filogenéticas em interfaces entre bordas florestais e matrizes antrópicas (floresta‐pasto e floresta‐eucalipto) a partir de modelos lineares generalizados mistos. Nós também comparamos estes índices entre diferentes coberturas de terra para avaliar qual destas melhor preserva a história filogenética das comunidades. Nós utilizamos tanto índices filogenéticos tradicionais, quanto aqueles corrigidos para a riqueza de espécies. Nossos resultados mostraram que a diversidade filogenética variou significativamente entre as coberturas de terra, mas isso não aconteceu quando removemos os efeitos associados à riqueza de espécies, o que sugere que todas as diferentes coberturas de terra preservam níveis similares de história evolutiva. Adicionalmente, nossos melhores modelos mostraram uma relação positiva entre a heterogeneidade da paisagem e os índices filogenéticos de diversidade e estrutura das comunidades de aves. Entretanto, a força dessas relações pode ser dependente da cobertura florestal. Em síntese, nosso trabalho destaca a influência da heterogeneidade da paisagem na diversidade e estrutura filogenética das comunidades de aves, o que reforça a necessidade de sua incorporação em estudos conservacionistas. Phylogenetic diversity varied significantly between land cover types, but this did not occur when we removed effects associated with species richness, suggesting that all land covers preserve similar levels of evolutionary history. Our best models showed a positive relationship between landscape heterogeneity and bird phylogenetic indexes of diversity and structure, but the strength of these relationships may be land‐cover dependent.